2021
DOI: 10.22374/jeleu.v4i3.117
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Remote Urology Outpatient Clinics during the COVID-19 Pandemic

Abstract: Introduction: The coronavirus (COVID-19) pandemic of 2020 had a major impact on NHS services. From the 23rd of March 2020, the Urology Department in Basingstoke initiated telephone-led consultation clinicsinstead of face-to-face outpatient appointments, in accordance with U.K. guidance.Objectives: To evaluate patient experience and satisfaction following the introduction of remote (telephone) consultations during the COVID-19 pandemic.Patients and methods: The first 200 remote patient appointments between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…While eight studies are from 2013, most studies were published quite recently in 2019 ( N = 7), 2020 ( N = 6), 2021 ( N = 16), and 2022 ( N = 9). Relocating care from the hospital to eHealth is the form of relocating that is most often examined within the studies identified ( N = 28) [ 26 53 ]. This is followed by relocating from the hospital to self-care ( N = 15) [ 54 67 ] and care at home ( N = 13) [ 30 , 68 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…While eight studies are from 2013, most studies were published quite recently in 2019 ( N = 7), 2020 ( N = 6), 2021 ( N = 16), and 2022 ( N = 9). Relocating care from the hospital to eHealth is the form of relocating that is most often examined within the studies identified ( N = 28) [ 26 53 ]. This is followed by relocating from the hospital to self-care ( N = 15) [ 54 67 ] and care at home ( N = 13) [ 30 , 68 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was true for all forms of relocation [ 27 30 , 32 34 , 38 , 41 , 42 , 45 , 47 , 49 , 52 54 , 58 60 , 65 67 , 69 , 70 , 73 , 78 , 82 , 84 86 , 88 , 90 , 93 , 94 ]. Citizens think of relocating as convenient because in most cases it saves travel time [ 26 , 29 , 53 ]. It saves costs [ 26 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations